Literatur Review Pemanfaatan Teknologi Pembelajaran Terhadap Hasil Belajar IPA di Sekolah Dasar - Mufidatul Ismi; Nadifah Nadifah; Nisa'ul Khoiriyah Hadi; Nurul Imamah; Yamin Yamin (Journal of Literature Review, 2026)
The rapid development of digital technology has brought significant changes to science learning processes in elementary schools. The utilization of learning technology provides teachers with opportunities to create more interactive, engaging, and student-centered learning experiences. This study aims to examine the impact of learning technology on science learning outcomes in elementary schools through a literature review approach. Data were collected from various relevant scientific articles and journals and analyzed using descriptive qualitative techniques through the stages of identification, classification, comparison, interpretation, and synthesis of research findings. The results indicate that the use of learning videos, animated videos, interactive multimedia, Wordwall applications, Genially, and other digital learning media contributes positively to improving learning outcomes, conceptual understanding, scientific literacy, learning motivation, learning interest, and student participation. The integration of technology with the Discovery Learning model has also been shown to enhance critical thinking and problem-solving skills through active student engagement in the learning process. However, its implementation still faces several challenges, including limited facilities, unequal access to technology, and varying levels of teachers’ digital competence. Therefore, adequate infrastructure and continuous improvement of teachers’ digital skills are needed to optimize the implementation of technology-based learning.